Use of anti-terrorism digital ecosystem in the fight against terrorism - Hadzic, Maja; Chang, Elizabeth (International Telework Academy, 2006)
In this paper, we propose an Anti-terrorist Digital Ecosystem (ATDES) that enables efficient terrorist identification and protection against terrorist attacks. An Anti-terrorist Digital Environment (ATDE) is designed as being populated by interconnected Anti-terrorist Digital Components (ATDC). ATDC are combined together to support collaboration, cooperation and sharing of available information between various regions, countries and even continents.ATDC may be any useful idea that can be digitalized, transported within the ecosystem and processed by humans or by computers. The key ATDC include ID databases that contain personal records, screening components that read personal records and match them with the available information from the ID databases and machine-readable personal records. The available information is put into one big virtual database and enables matching of personal records.If the available information is to be shared between various ID information resources, standardization of data needs to take place. Ontologies can be used for this purpose. Instantiation of the Ontology concepts result in ID Ontologies that act as personal records. Because Ontology files are machine readable, it is possible to do the matching of personal records with the available ID records from the networked ID databases and to action the results.The significance of this research lies in the unification of the advances of the Ontology technology and Ecosystem paradigm for the purpose of creating a more secure environment in which to fight against terrorism.